TRAINING FOR THE FUTURE TEACHER WITH THE HELP OF NEW PEDAGOGICAL TECHNOLOGIES - Savchenko, L.A. (Pedagogy of Higher and Secondary Education, 2004)
The article deals with some problems concerning future teachers’ professional training by means of new pedagogical technologies.